Experimental determination of gas diffusivity in liquids—A review. (20th April 2021) - Upreti, Simant R.; Mehrotra, Anil K.
Abstract: Unit operations and processes abound with gas diffusion in liquids, which is a sophisticated phenomenon in which mass transfer is characterized by diffusion coefficient or diffusivity. Compared to diffusion in gas phase, the closely packed liquid molecules strongly influence diffusive mass transfer to the extent that it is impossible to have a general theory for a reasonably accurate estimation of diffusivity in liquids. This situation is further compounded by the fact that diffusivity cannot be measured directly but can only be estimated indirectly with the help of a number of observable properties (eg, mass, volume, pressure, etc). This fact gives rise to a myriad of experimental methods for the determination of gas diffusivity in liquids. These methods report gas diffusivities over widely varying ranges of temperature, pressure, and liquid composition. To provide a state‐of‐the‐art knowledge base for such methods is the objective of this work. The focus is on gas diffusion in binary gas‐liquid systems. Starting with necessary theoretical foundations, we provide a systematic categorization of these methods based on the property change utilized for diffusivity determination. The methods are then concisely described, and the diffusivity data are summarized for over 160 gas‐liquid systems at different temperature and pressure conditions. Empirical correlations are provided for different gas‐liquid systems, which could be used for interpolating gas diffusivity as a function of temperature, pressure, and composition.